2013
DOI: 10.1371/journal.pgen.1003975
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid-Specific Deletion of Klotho Unravels a Novel Calcineurin-Dependent FGF23 Signaling Pathway That Regulates PTH Secretion

Abstract: Klotho acts as a co-receptor for and dictates tissue specificity of circulating FGF23. FGF23 inhibits PTH secretion, and reduced Klotho abundance is considered a pathogenic factor in renal secondary hyperparathyroidism. To dissect the role of parathyroid gland resident Klotho in health and disease, we generated mice with a parathyroid-specific Klotho deletion (PTH-KL−/−). PTH-KL−/− mice had a normal gross phenotype and survival; normal serum PTH and calcium; unaltered expression of the PTH gene in parathyroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
120
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(130 citation statements)
references
References 35 publications
6
120
1
3
Order By: Relevance
“…17) In addition, Fgf23 was recently shown to inhibit the secretion of parathyroid hormones from parathyroid glands, both in α Klotho-dependent and -independent manners. 23) Our present data suggested that the activation of Fgf receptor by Fgf23 is essential for the activity of Fgf23 in macrophages. Therefore, Fgf23 increases the number of macrophages and induces the expression of TNF-α via the signaling of Fgf receptor in an α Klotho-independent manner.…”
supporting
confidence: 52%
“…17) In addition, Fgf23 was recently shown to inhibit the secretion of parathyroid hormones from parathyroid glands, both in α Klotho-dependent and -independent manners. 23) Our present data suggested that the activation of Fgf receptor by Fgf23 is essential for the activity of Fgf23 in macrophages. Therefore, Fgf23 increases the number of macrophages and induces the expression of TNF-α via the signaling of Fgf receptor in an α Klotho-independent manner.…”
supporting
confidence: 52%
“…Providing only the cKL form in a sustained manner created the ability to test this factor's activity and pharmacologic potential in the absence of mKL in an environment of hyperphosphatemia. Similar to mice conditionally lacking parathyroid aKL expression, aKLnull mice may maintain low parathyroid hormone (PTH) levels by using an aKL-independent calcineurin-mediated FGF23 signaling pathway to suppress the secretion of PTH, 53 which could occur, in part, with the known negative feedback loop between 1,25D and PTH. Indeed, we showed that cKL, likely through the elevated FGF23, reduced serum 1,25D in WT mice, leading to hyperparathyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Klotho activity has also been implicated as fundamental for the stimulation of PTH secretion during hypocalcaemic conditions (Imura et al 2007), although the underlying mechanism has been challenged (Martuseviciene et al 2011). An in vitro study has demonstrated that blocking a parathyroid-FGF23 signalling pathway, involving calcineurin, led to abolition of FGF23-induced suppresion of PTH secretion (Olauson et al 2013). Thus, this pathway could be another future molecular target pathway for the treatment of parathyroid carcinoma.…”
Section: Molecular Targeted Treatmentmentioning
confidence: 99%